Cooperation, Conflict, and Power in the Absence of Property Rights - Skaperdas, Stergios (American Economic Review, 1992)
This paper examines interaction in the absence of property rights when agents face a trade-off between productive and coercive activities. In this setting, conflict is not the necessary outcome of one-time interaction, and cooperation is consistent with domination of one agent over another. Other things being equal, an agent's power, a well-defined concept in this paper, is inversely related to an agent's resources when resources are valued according to marginal-productivity theory. Some implications for the evolution of property rights are drawn. The model is applicable to a variety of situations in which directly unproductive activities are prevalent.